(untitled) (Научни трудове на УНСС, 2024)
The intersection of sustainability and sports has emerged as a pivotal arena for exploring the evolving dynamics of contemporary society. In the context of Formula 1, sustainability-related norms and policies have started to affect sponsorship relations. The study aims to examine how F1 teams’ sustainability strategies have impacted their sponsorship policies. To get a better understanding of views, motives and activities related to the adaptation of the sustainability concept to their sponsorship propositions, semi-structured interviews with commercial managers from three F1 teams were conducted. Facing diverse stakeholder pressures and expectations, as well as the newly adopted internal policies, the teams’ commercial departments have embraced sustainable development for strategic and instrumental reasons. The adjustments concentrate on aligning the teams’ sponsorship practices with their management vision and sustainability prioritisation. Simultaneously, they also aim to support the implementation of the teams’ sustainability commitments. However, the data suggests that sustainability is not yet consistently a decisive factor in F1 sponsorships. That sparks ethical dilemmas, as teams continue partnering with sponsors from contradictive industries, highlighting a paradox between the sport’s dedication to sustainability and its reliance on commercial ventures. The paper unpacks the under-researched relationship between the adoption of sustainability norms and policies and their practical manifestations in organisational sponsorships.